1E.001 Health metrics in Victorian family violence homicides. (14th March 2021) - Sarkar, Reena; Ozanne-Smith, Joan; Bassed, Richard
Abstract : Introduction: The International Classification of Diseases (ICD)-10 coding describes injury patterns for compilation of national mortality statistics published by the World Health Organisation (WHO). ICD-10 is exposed to many sources of variability including interpretation of the medical cause of death (MCoD) statements and multiple injuries in fatal assaults. We aim to identify the main sources of discrepancies between the ICD-10 statistics and autopsy reports in family violence (FV) homicides. The purpose is to identify reliability problems of injury ascertainment using ICD-10 and inform precise methods in describing MCoD injuries in FV. Methods: Victorian FV homicides, January 2006 to December 2018, were identified by screening closed cases after coroners' investigations of assaults for eligible victim-offender/family-like relationship. Australian Bureau of Statistics assigned ICD-10 codes were examined in the context of all injury patterns. The MCoD statements and information in autopsy reports was compared to the ICD-10 coding for underlying and MCoD. Results: A total of 195 FV homicides were identified during the 12-year period. Substantial discrepancies were found in usage of nonspecific codes and external cause/intent assignment. These included 15/195 (7.69%) of cases where underlying codes differed by intent. Conclusions: This is a population study investigating ICD-10 coding in Victorian FV homicides over a 12-year period. Forensic pathologists should classify specific information available on autopsy reports in a format compatible with ICD coding and WHO death registration. This research may inform a standardised approach towards data specificity in all cause injury deaths, with potential implications for injury prevention and the justice system.